2009
DOI: 10.1055/s-0029-1241733
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Diabetes Recurrence in Women with Class A1(Diet-Treated) Gestational Diabetes

Abstract: We sought to evaluate the likelihood of recurrent diabetes in women with a prior history of diet-treated (class A(1)) gestational diabetes mellitus (GDM). In a retrospective cohort analysis, nulliparous women diagnosed based upon National Diabetes Data Group criteria with diet-treated GDM who had recurrent diabetes in a subsequent pregnancy were compared with those who did not have recurrent diabetes. The probability of recurrent diabetes was calculated using maternal age at first pregnancy, interpregnancy int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…Our review identified a number of studies that presented data on birth spacing and adverse maternal outcomes, but did not meet our inclusion criteria because of methodological concerns that limited their interpretability for informing development of recommendations on birth spacing for the United States. Several studies examined interbirth interval (rather than interpregnancy interval), [43][44][45][46][47][48][49][50][51][52][53] presented crude results only (no adjustment for maternal age), 22,43,49,52,54,55 or did not account for a potential non-linear relationship between interpregnancy interval and health outcome by either assuming that interpregnancy interval had a linear association with risks of adverse outcomes or using a reference category with no upper bound. 20,22,46,47,[56][57][58] Nevertheless, the conclusions of the excluded studies are consistent with our findings that short interpregnancy interval is associated with increased risk of uterine rupture among women with prior caesarean birth 46,47,49 and placental abruption, 17,52 as well as decreased risk of preeclampsia or other hypertensive disorders of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review identified a number of studies that presented data on birth spacing and adverse maternal outcomes, but did not meet our inclusion criteria because of methodological concerns that limited their interpretability for informing development of recommendations on birth spacing for the United States. Several studies examined interbirth interval (rather than interpregnancy interval), [43][44][45][46][47][48][49][50][51][52][53] presented crude results only (no adjustment for maternal age), 22,43,49,52,54,55 or did not account for a potential non-linear relationship between interpregnancy interval and health outcome by either assuming that interpregnancy interval had a linear association with risks of adverse outcomes or using a reference category with no upper bound. 20,22,46,47,[56][57][58] Nevertheless, the conclusions of the excluded studies are consistent with our findings that short interpregnancy interval is associated with increased risk of uterine rupture among women with prior caesarean birth 46,47,49 and placental abruption, 17,52 as well as decreased risk of preeclampsia or other hypertensive disorders of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…12,21,50,51,59,60 However, in contrast to the studies in our review, several excluded studies suggested that risks of obesity and gestational diabetes may actually increase with longer (not shorter) interpregnancy interval. 43,44,54,56 In addition, both short and long interpregnancy intervals were linked with increased risk of placenta previa, 53 while women with placenta accreta had a shorter average interpregnancy interval than controls. 20 Limitations of studies specific to each key question are briefly described in Tables 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Women with GDM are also at increase risk of development of permanent diabetes in future [11,12]. Poorly managed GDM results in number of undesirable maternal-foetal events such as miscarriages, lengthened labour pain, caesarean section, macrosomia, shoulder dystocia, neonatal hypoglycaemia, still birth and neonatal death [7,[13][14][15][16][17][18]. Well controlled GDM results in reduction of these unfavourable outcomes [19].…”
Section: Introductionmentioning
confidence: 99%
“…We examined and contrasted four different approaches to classifying women’s diabetes status: BC data alone, HD data alone, both sources hierarchically combined in which a diagnosis of CDM from either source took priority over a diagnosis of GDM, and both sources combined [18] in which only pregnancies with complete agreement in diagnosis between sources were included. We then examined selected characteristics of women with different patterns of GDM/CDM recurrence and non-recurrence.…”
Section: Introductionmentioning
confidence: 99%